2022
DOI: 10.1021/acsphotonics.2c00370
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pockels Effect in AlN Microring Resonator Modulators Based on AlGaN/AlN Multiple Quantum Wells

Abstract: AlN-on-sapphire is a promising integrated photonic platform for operation over a wide wavelength range from ultraviolet to infrared. However, this platform suffers from a weak second-order electro-optic effect, also known as the Pockels effect. Here, we demonstrate an enhanced Pockels effect by utilizing AlGaN/AlN multiple quantum wells (MQWs) regrown on the AlN layer. This enhancement is attributed to the large built-in polarization field in the MQWs, which results in a higher second-order susceptibility in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Due to low optical loss and relatively large EO coefficient, AlN can be used to achieve electro-optic devices [ 185 ]. In 2012, Xiong et al demonstrated an AlN-based microring modulator [ 186 ].…”
Section: Materials Platformsmentioning
confidence: 99%
“…Due to low optical loss and relatively large EO coefficient, AlN can be used to achieve electro-optic devices [ 185 ]. In 2012, Xiong et al demonstrated an AlN-based microring modulator [ 186 ].…”
Section: Materials Platformsmentioning
confidence: 99%